2019
DOI: 10.3390/molecules24122230
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Migraine Effect of the Herbal Combination of Chuanxiong Rhizoma and Cyperi Rhizoma and UPLC-MS/MS Method for the Simultaneous Quantification of the Active Constituents in Rat Serum and Cerebral Cortex

Abstract: Chuanxiong Rhizoma and Cyperi Rhizoma (CRCR), an ancient and classic formula comprised of Chuanxiong Rhizoma and Cyperi Rhizoma in a weight ratio of 1:2, has long been used for curing migraine. This study aimed to explore their anti-migraine effect and active constituents. A nitroglycerin (NTG)-induced migraine model in rats was established to evaluate pharmacological effects. Cerebral blood flow was detected by a laser Doppler perfusion monitor. The levels of endothelin-1 (ET-1), γ-aminobutyric acid (GABA), n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…We proved that Chuanxiong Rhizoma-Cyperi Rhizoma combination alleviates the migraine by regulating of increase of vasomotor factors such as CGRP, NOS, NO, ET. These effects are similar to those previously reported by Wu et al [5].…”
Section: Effects Of Alcoholic Extracts From Chuanxiong Rhizoma-cyperi...supporting
confidence: 93%
See 1 more Smart Citation
“…We proved that Chuanxiong Rhizoma-Cyperi Rhizoma combination alleviates the migraine by regulating of increase of vasomotor factors such as CGRP, NOS, NO, ET. These effects are similar to those previously reported by Wu et al [5].…”
Section: Effects Of Alcoholic Extracts From Chuanxiong Rhizoma-cyperi...supporting
confidence: 93%
“…The use of Chuanxiong Rhizoma-Cyperi Rhizoma combination is first stated in Danxi Xinfa (a comprehensive medical book written by Zhu Zhenheng in 1481) for the alleviation of headache with a syndrome of phlegm syncope and migraine headache [4]. Pharmacological studies have shown that the combination of Chuanxiong Rhizoma and Cyperi Rhizoma can reduce the number of writhing times in dysmenorrhea rat model to varying degrees, can prolong the writhing latency and can reduce the whole blood viscosity of rats [5]. Besides, it can also treat migraines caused by vegetative nerve functional and vasomotor disorders [6].…”
Section: Introductionmentioning
confidence: 99%
“…In our future report, we aim to show the multi-ion channel mechanism of DFD. In addition, with the development of mass spectrometry, multiple constituents of the components of DFD have been analyzed and characterized in recent years [29][30][31][32][33][34]. Modern pharmacological studies have shown that the components of DFD have anti-inflammatory [35][36][37][38][39], antioxidative stress [40][41][42], and myocardial protection [42][43][44][45] effects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Xiang Fu Chuan Xiong Cha, an ancient formula, composed of Cyperi Rhizoma and Chuanxiong Rhizoma at a 2:1 weight ratio, was used for curing migraines and headaches. A recent animal study demonstrated that Cyperi Rhizoma and Chuanxiong Rhizoma (CRCR) significantly increased cerebral blood flow and decreased several substances involved in neurogenic inflammation, thereby relieving migraines [43]. Fructus Viticis (Man jing zi) is another traditional Chinese medicine that is commonly used for curing migraines and headaches.…”
Section: Migraine-like Syndromementioning
confidence: 99%